Upaya Meningkatkan Kompetensi Logaritma Siswa Kelas X IPA dengan Strategi Pembelajaran Aktif pada SMA Narada Jakarta - Mukhtar, Ang Baben Haidar; Hasbullah, Hasbullah (Jurnal Gemaedu, 2018)
This study aims to improve the logarithmic competence of class X IPA students with active learning strategies in Narada Jakarta High School students. The research method used is classroom action research through 2 cycles and in each cycle includes activities of planning, implementation, observation and reflection. The results showed an increase in mastery of this competency starting from the first cycle of students can increase by 28% from the initial conditions of the conditions in the first cycle after the action in the second cycle increased by 30%. From the results of this class action research the researcher recommends policy making or implementing learning in this case, namely the instructor to teach learning material in small groups and with techniques to activate students